Pairing Microwell Arrays with an Affordable, Semiautomated Single-Cell Aspirator for the Interrogation of Circulating Tumor Cell Heterogeneity. (April 2020) - Tokar, Jacob J.; Stahlfeld, Charlotte N.; Sperger, Jamie M.; Niles, David J.; Beebe, David J.; Lang, Joshua M.; Warrick, Jay W.
Comprehensive analysis of tumor heterogeneity requires robust methods for the isolation and analysis of single cells from patient samples. An ideal approach would be fully compatible with downstream analytic methods, such as advanced genomic testing. These endpoints necessitate the use of live cells at high purity. A multitude of microfluidic circulating tumor cell (CTC) enrichment technologies exist, but many of those perform bulk sample enrichment and are not, on their own, capable of single-cell interrogation. To address this, we developed an affordable semiautomated single-cell aspirator (SASCA) to further enrich rare-cell populations from a specialized microwell array, per their phenotypic markers. Immobilization of cells within microwells, integrated with a real-time image processing software, facilitates the detection and precise isolation of targeted cells that have been optimally seeded into the microwells. Here, we demonstrate the platform capabilities through the aspiration of target cells from an impure background population, where we obtain purity levels of 90%–100% and demonstrate the enrichment of the target population with high-quality RNA extraction. A range of low cell numbers were aspirated using SASCA before undergoing whole transcriptome and genome analysis, exhibiting the ability to obtain endpoints from low-template inputs. Lastly, CTCs from patients with castration-resistant prostate cancer were isolated with this platform and the utility of this method was confirmed for rare-cell isolation. SASCA satisfies a need for an affordable option to isolate single cells or highly purified subpopulations of cells to probe complex mechanisms driving disease progression and resistance in patients with cancer.